Time Consistency of Fiscal and Monetary Policy: A Comment - Calvo, Guillermo A.; Obstfeld, Maurice (Econometrica, 1990)
IN AN IMPORTANT recent contribution, Persson, Persson, and Svensson (1987) (hereafter PPS) suggest that through careful restructuring of its nominal and real debt obligations, a government may be able to induce future governments to follow the monetary and fiscal policies that it regards as optimal today. The PPS argument builds on Lucas and Stokey's (1983) demonstration that in a special nonmonetary setting, the time inconsistency of optimal fiscal policy can be avoided through managing the term structure of real government obligations to the public. The basic idea of the PPS scheme for monetary economies is disarmingly intuitive: in addition to continually restructuring nominal and real debt obligations a la Lucas-Stokey, each government must ensure that the next government inherits a stream of nominal claims on the public whose present discounted value equals the stock of money. This equality, PPS argue, removes the incentive for surprise inflation or deflation, because such surprises would not affect the real net worth of the government. This note shows that the PPS prescription for avoiding time inconsistency, appealing as it is, is not generally sufficient. Even under the debt restructuring they recommend, optimal policy is likely to be time inconsistent. The main reason why their scheme fails is that the restrictions it imposes on government asset stocks satisfy first-order but not second-order conditions for an optimum. Because of the complex interactions between the current price level and future interest rates, a government can raise its objective function by moving several variables at once away from the levels planned by the previous government, even though price-level changes alone would not affect government net worth. We develop our argument using the model, notation, and equation numbers of PPS, to which the reader is referred for details. The maximization problem associated with